2019
DOI: 10.1155/2019/6384278
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Inhibits the Proliferation of Triple-Negative Breast Cancer Cells through a Mechanism Involving the Proinflammatory Cytokines IL-1βand TNF-α

Abstract: Triple-negative breast cancer (TNBC) is one of the most aggressive tumors, with poor prognosis and high metastatic capacity. The aggressive behavior may involve inflammatory processes characterized by deregulation of molecules related to the immunological responses in which interleukin-1β(IL-1β) and tumor necrosis factor-α(TNF-α) are involved. It is known that calcitriol, the active vitamin D metabolite, modulates the synthesis of immunological mediators; however, its role in the regulation of IL-1βand TNF-αin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Using the cancer genome atlas (TCGA) database, breast cancer patients with high levels of mRNA expression of IL1B were shown to have a better prognosis than those with low levels [ 30 ]. Similarly, the quantification of IL1B mRNA by qPCR in cervical cancer biopsies showed an increase in the risk of progression of pre-neoplasic lesions in women with lower IL1B expression [ 31 ].…”
Section: Il-1β As a Cancer Marker?mentioning
confidence: 99%
“…Using the cancer genome atlas (TCGA) database, breast cancer patients with high levels of mRNA expression of IL1B were shown to have a better prognosis than those with low levels [ 30 ]. Similarly, the quantification of IL1B mRNA by qPCR in cervical cancer biopsies showed an increase in the risk of progression of pre-neoplasic lesions in women with lower IL1B expression [ 31 ].…”
Section: Il-1β As a Cancer Marker?mentioning
confidence: 99%
“…On the other hand, 1,25(OH)2D modulates the synthesis of immunological mediators [65]. It was shown that 1,25(OH)2D and its analogue, EB1089, inhibited proliferation of the TNBC cell lines SUM-229PE and HCC1806 that expressed VDR, IL-1β, and TNF-α receptors [66]. These studies also showed that synthesis of IL-1β and TNF-α was stimulated by 1,25(OH)2D and EB1089.…”
Section: Oxidative Stress Proliferation Differentiation and Inflammmentioning
confidence: 99%
“…Moreover, the co-treatment with 1,25(OH) 2 D and TNF-α inhibited metalloprotease-9 (MMP-9) and monocyte chemoattractant protein-1 (MCP-1) protein expression, otherwise hyperactivated in presence of TNF-α alone, by demonstrating a further role of vitamin D in the regulation of infiltration, migration and cancer invasiveness [174]. Conversely, human breast cancer cells treated with 1,25(OH) 2 D showed decreased proliferation, in part induced by the reduced TNF-α and IL-1β synthesis, by demonstrating that even drastic deregulation of immune modulators may contribute to cancer progression [137].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Anticancer activity of vitamin D has been largely studied in different types of tumors, elucidating its pivotal role in cancer progression and invasion [ 134 ]. It has been reported that vitamin D inhibits colorectal, prostate and breast cancer cells growth by controlling cell proliferation [ 11 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ] through cell cycle arrest [ 144 , 147 , 148 , 149 , 150 ], by regulating cell death through apoptosis [ 54 , 144 , 147 , 151 , 152 , 153 ] and autophagic processes [ 154 , 155 ], and by modulating inflammatory processes implicated in immune infiltration and tumor invasiveness [ 134 , 137 , 150 ].…”
Section: Vitamin D and Cancer: Molecular Mechanisms In In Vivo Andmentioning
confidence: 99%